2014
DOI: 10.1111/pde.12481
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma‐Associated Stevens–Johnson Syndrome in Children: Retrospective Review of Patients Managed With or Without Intravenous Immunoglobulin, Systemic Corticosteroids, or a Combination of Therapies

Abstract: Administration of intravenous immunoglobulin (IVIG) to patients with Stevens-Johnson syndrome (SJS) has been controversial. The objective of this study was to evaluate the effectiveness of IVIG, systemic corticosteroids, or both in treating Mycoplasma pneumoniae-associated SJS (mpSJS). Retrospective series of 10 pediatric mpSJS cases were stratified into four treatment groups: IVIG alone, IVIG and systemic corticosteroids together, systemic corticosteroids alone, and supportive care. The efficacy of therapy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…Total 15 studies observed either cessation time or hospitalization length[9, 2527, 31, 32, 36–44]. Of these, 3 studies recruited patients with SJS only[9, 36, 37], 5 studies chose TEN patients only[26, 31, 38–40] and 7 studies imposed no restrictions about patients recruitment[25, 27, 32, 41–44].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total 15 studies observed either cessation time or hospitalization length[9, 2527, 31, 32, 36–44]. Of these, 3 studies recruited patients with SJS only[9, 36, 37], 5 studies chose TEN patients only[26, 31, 38–40] and 7 studies imposed no restrictions about patients recruitment[25, 27, 32, 41–44].…”
Section: Resultsmentioning
confidence: 99%
“…Two common variables, the time to arrest progression and the hospitalization length, were utilized to measure the improvements of patients. A small part of studies that reported the time of progression arrest by describing when fever control[9], skin healing[31] and re-epithelialization[32] occurred were also included, because these descriptions were supposed to reflect to what magnitude did IVIG treatment accelerate the improvement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Report by Stevens Johnson Syndrome foundation (SJSF), has shown that commonly used over-the-counter medications like paracetamol, amoxicillin, and ibuprofen, and herbal products with Ginseng can trigger SJS and TEN [23,24]. SJS has been tailored to viral and Mycoplasma pneumonia without previous sensitization [19,[25][26][27][28][29][30]. Studies in immunicompromized patients show that they are more susceptible to SJS [18,[30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…23,24 SJS has been tailored to viral and Mycoplasma pneumonia without previous sensitization. 19,[25][26][27][28][29][30] Studies in immunicompromized patients show that they are more susceptible to SJS. 18,[30][31][32][33][34][35] This suggests genetic inclination to the varying manifestations of SJS.…”
Section: Discussionmentioning
confidence: 99%